2021
DOI: 10.1108/ijefm-10-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Staging city events in public spaces: an urban design perspective

Abstract: PurposeThere are two main aims of this conceptual paper. The first is to explore the issues associated with staging events in public spaces, and to produce a typology of different event spaces. The second is to explore if and how events should be designed into parks, streets and squares and whether this might reduce some of the negative impacts and associated user conflicts.Design/methodology/approachThe paper analyses the history, drivers and effects of using public spaces as venues and examines the reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Street activations can bring rise to informal economies, such as street performers and informal vendors. (Smith et al, 2021). Inam (2019) discussed the large volume of vacant parking lots in the NIA of Thorncliffe Park.…”
Section: Equitable Public Spacementioning
confidence: 99%
“…Street activations can bring rise to informal economies, such as street performers and informal vendors. (Smith et al, 2021). Inam (2019) discussed the large volume of vacant parking lots in the NIA of Thorncliffe Park.…”
Section: Equitable Public Spacementioning
confidence: 99%
“…Events open up opportunities for new interpretations of public spaces [9]. Related spatial organization reveals how a festival can facilitate social interaction at a local scale [10].…”
Section: Festival and Urban Spacementioning
confidence: 99%
“…So, it is essential to consider how the crowd and temporary structures interact and how static and dynamic aspects interact. (Smith et al, 2021) Many different stakeholder groups can be recognised for any event in a city.…”
Section: Event Categoriesmentioning
confidence: 99%
“…Zhou et al (2017) investigate attempts by medium-sized Chinese cities to use events to attract people and create markets. Smith et al (2021) write about staging city events in urban public spaces. This article is the only study found on events from an urban design perspective.…”
Section: Events Studiesmentioning
confidence: 99%
See 1 more Smart Citation